Characterization of a pediatric population during the COVID-19 pandemic in a Brazilian Cancer Center - Talita Mariana Wicthoff Raniero, Jessica; Spitti Rocha , Poline; Eduardo Ramos Fernandes, Carlos; José Clemente Duarte, Maria; Quinto de Souza , Fabiana; Cristina Breves, Elaine; Mariano Palanch Piotto, Luciana; Maria Lima da Costa, Cecilia (Seven Editora, 2023)
Introduction: There is divergence between the severity and mortality rate in oncological children depending on the country or the health center studied, therefore, it was identified the need to develop a study, with the objective of characterizing this population and identifying the reason why the patient is submitted to the examination for research of COVID-19 and its clinical outcome. Methods: Descriptive, retrospective study carried out between February 2020 to February 2022. Patients younger than 18 years of age during treatment at a Brazilian Cancer Center. Results: 668 patients were identified. Divided into two groups: Group 1, 122 (18%) presenting clinical symptoms and Group 2, with 546 (82%) patients who submitted to exam collection prior to the surgical procedure and/or imaging exam. The median age between the groups was 9 and 7 years, respectively. Almost all patients in Group 1, had symptoms related to COVID-19 and all who had feverish neutropenia belonged to this group. The most prevalent underlying disease in Group 1, was hematological and in Group 2, venous malformation. Of the total, 27 (4%) patients tested positive and only one patient died. Conclusion: COVID-19 affected both genders and its severity were independent of underlying disease or age. The protection and prevention measures throughout the period of the pandemic, allowed the low rate of contamination and severity and mortality in the patients of this study not to interrupt the treatment and its follow-up. DOI: https://doi.org/10.56238/tfisdwv1-156